A review of the effectiveness of game-based training for dismounted soldiers. (October 2014) - Whitney, Susannah J.; Temby, Philip; Stephens, Ashley
Computer games are increasingly being used by armed forces to supplement conventional training methods. However, despite considerable anecdotal claims about their training effectiveness, empirical evidence is lacking. This paper critically reviews major studies conducted in the past decade that have examined game-based training with dismounted soldiers. The findings indicate that these studies are characterized by methodological limitations and that the evidence regarding the effectiveness of game-based training for this military population is not compelling. Furthermore, due to methodological limitations with the studies, the possibility of negative training effects cannot be discounted. The paper concludes with implications for the scientific and military communities, as well as recommendations for the conduct of future studies in this area.